2008
DOI: 10.1007/s10530-008-9360-9
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of ancient Lake Titicaca by the globally invasive Physa acuta (Gastropoda: Pulmonata: Hygrophila)

Abstract: A vital population of Physa acuta, a globally invasive species of freshwater gastropods was dicovered in ancient Lake Titicaca in April 2007. The population was found near Chucuito (Bahia de Puno) on the Peruvian side in close proximity to a boat landing of the aquaculture facility of the University of Puno. Physids occured in great abundances at this site on macrophytes in depths from 0 to 2 m. Physa acuta was associated with members of the Heleobia andicola species complex as well as with Heleobia otorni, Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 22 publications
1
50
0
1
Order By: Relevance
“…What Old Romans called ''Mare Nostrum'' was crossed by several trade routes and people living on its shores have been sailing across it since at least 5,000 years, founding settlements and actively transporting goods (and drinking water) all around the lands surrounding this sea (Abulafia, 2011). Further to historical reasons, other more recent human activities still contribute to freshwater organisms dispersal: construction of canals connecting separated watersheds (Dumont, 1995), recreational boating (Albrecht et al, 2009;Bruckerhoff et al, 2014), trade in ornamental species for aquaria (Padilla & Williams, 2004;Marrone & Naselli-Flores, 2011;Havel et al, 2014), and ecotourism and/or scientific field-work (Waterkeyn et al, 2010) have been found to be responsible of dispersal and new species (even invasive) introductions. Trading of living fish for sport and professional fishing can be also responsible for the accidental introductions of (micro)organisms and a huge number of nonindigenous species are reported as ''invaders'' in freshwater ecosystems at a high frequency (Ruiz & Carlton, 2003;Havens & Beaver, 2014).…”
Section: Dispersal By Human Activitiesmentioning
confidence: 99%
“…What Old Romans called ''Mare Nostrum'' was crossed by several trade routes and people living on its shores have been sailing across it since at least 5,000 years, founding settlements and actively transporting goods (and drinking water) all around the lands surrounding this sea (Abulafia, 2011). Further to historical reasons, other more recent human activities still contribute to freshwater organisms dispersal: construction of canals connecting separated watersheds (Dumont, 1995), recreational boating (Albrecht et al, 2009;Bruckerhoff et al, 2014), trade in ornamental species for aquaria (Padilla & Williams, 2004;Marrone & Naselli-Flores, 2011;Havel et al, 2014), and ecotourism and/or scientific field-work (Waterkeyn et al, 2010) have been found to be responsible of dispersal and new species (even invasive) introductions. Trading of living fish for sport and professional fishing can be also responsible for the accidental introductions of (micro)organisms and a huge number of nonindigenous species are reported as ''invaders'' in freshwater ecosystems at a high frequency (Ruiz & Carlton, 2003;Havens & Beaver, 2014).…”
Section: Dispersal By Human Activitiesmentioning
confidence: 99%
“…This number of reference sequences would be sufficient for distinct species specific clades to emerge during phylogenetic analysis and definitively identify sequences generated in this current study. Each of these reference sequences was considered as putative throughout the analysis and were chosen because they were generated for studies focused primarily on the molecular identification and the evolutionary relationships of Radix species particularly from the following works: Albrecht et al, 2009;Bargues et al, 2001;Bolotov et al, Christiansen et al, 2014;Cipriani et al, 2011;Correa et al, 2011;Dung et al, 2013;Ferreira et al, 2014;Ferté et al, 2005;Huňova et al, 2012;Jouet et al, 2008Jouet et al, , 2010Kaset et al, 2009;Liu et al, 2010;Patel et al, 2015;Pfenninger et al, 2011;Novobilsky et al, 2014;Schniebs et al, 2011Schniebs et al, , 2013Vinarski et al, 2015;von Oheimb et al, 2011; Therefore the sequences used for inter-species comparisons were considered to be representative of taxa alone and were not used to make biogeographical inferences.…”
Section: Collectionmentioning
confidence: 99%
“…It is known as a rapid (re)coloniser of freshwater systems where it is exposed to variable environmental conditions (Chlyeh et al, 2006). It can efficiently disperse via water ( Van de Meutter, Stoks & De Meester, 2006) and has been found to be carried in plant material on boats between lakes (Albrecht et al, 2009). Anecdotal evidence suggests that it may also be dispersed by waterbirds (e.g.…”
Section: Introductionmentioning
confidence: 99%